2022
DOI: 10.1542/peds.2022-057780
|View full text |Cite
|
Sign up to set email alerts
|

Advertising and Young People’s Critical Reasoning Abilities: Systematic Review and Meta-analysis

Abstract: BACKGROUND AND OBJECTIVES: Young people are exposed to an abundance of advertising for unhealthy products (eg, unhealthy foods, tobacco, alcohol). Because of their developing cognition, children may not be able to understand the intent of advertising. However, advertising restrictions often assume that adolescents have critical reasoning capacity and can resist the effects of advertising. This review seeks to assess whether the evidence supports this assumption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 84 publications
0
6
0
1
Order By: Relevance
“…According to 2021 UK data, 12 just under half of 10–15‐year‐olds search engine users can correctly identify adverts on Google searches, about half know that not all sites can be trusted, and two‐thirds recognize that vloggers (video bloggers) and influencers can be sponsored to promote products or brands. While recognition of marketing is essential for activating cognitive defenses against its harmful influence, 13 the unique developmental stage of adolescence—including increased susceptibility to risk taking, establishment of social identities, and desire for acceptance from peers—makes this age group particularly vulnerable to advertisers' messaging despite their advanced cognitive development relative to younger children 14–16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to 2021 UK data, 12 just under half of 10–15‐year‐olds search engine users can correctly identify adverts on Google searches, about half know that not all sites can be trusted, and two‐thirds recognize that vloggers (video bloggers) and influencers can be sponsored to promote products or brands. While recognition of marketing is essential for activating cognitive defenses against its harmful influence, 13 the unique developmental stage of adolescence—including increased susceptibility to risk taking, establishment of social identities, and desire for acceptance from peers—makes this age group particularly vulnerable to advertisers' messaging despite their advanced cognitive development relative to younger children 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…While recognition of marketing is essential for activating cognitive defenses against its harmful influence, 13 the unique developmental stage of adolescenceincluding increased susceptibility to risk taking, establishment of social identities, and desire for acceptance from peers-makes this age group particularly vulnerable to advertisers' messaging despite their advanced cognitive development relative to younger children. [14][15][16] Additionally, when on social media, adolescents can experience bullying, sexual harassment, exclusion, hate messages, exposure to inappropriate content such as self-harm strategies, and sleep problems, which can lead to stress, low mood, depression, injury, and even death. 1,17 Exposure to marketing and harmful content can also be further exacerbated by peers' interactions and the use of real-time personalized algorithms that rely on extensive collections of personal data such as emotions, responses, preferences, behavior, and location.…”
mentioning
confidence: 99%
“…Furthermore, these outcomes are not distributed equally within society, demonstrating a socioeconomic gradient where those in lower income groups are at higher risk 2 . While adolescents are significantly affected by excessive weight and related behaviors, they also experience this in the context of living through a unique developmental stage, characterized by increased susceptibility to risk‐taking, the establishment of identity, and desire for acceptance from peers, making the drivers of overweight and obesity in this age group particularly complex 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…2 While adolescents are significantly affected by excessive weight and related behaviors, they also experience this in the context of living through a unique developmental stage, characterized by increased susceptibility to risk-taking, the establishment of identity, and desire for acceptance from peers, making the drivers of overweight and obesity in this age group particularly complex. 3,4 With this in mind, there is increasing recognition in policy development and the research that informs it of the need to incorporate youth perspectives in the policies and programs designed to address issues relevant to their cohort. 5 A related publication by a number of this paper's co-authors 6 reported that collaboration with youth as equitable partners, rather than as the subjects or recipients of policy or programs, yields a contextualized and practical approach to problem-solving and is an empowering process for the youth involved.…”
mentioning
confidence: 99%
“…[5][6][7] Children are vulnerable to marketing due to their limited ability to understand the persuasive purpose of advertising. 8 This is exacerbated when food companies promote products using appealing marketing techniques, like cartoon characters or popular athletes. 9,10 Adolescents are susceptible to food marketing due to their neurocognitive and psychosocial development, which includes their growing independence, susceptibility to peer influence and desire to fit in.…”
Section: Introductionmentioning
confidence: 99%